Annealing-induced tunable bandgap and photoluminescence of (InGa)2O3 films deposited by magnetron sputtering. (April 2023) - Zhang, Ruixin; Shen, Longhai; Kuang, Ye; Liu, Zitong; Tian, Hui; Wu, Lijun; Li, Quanjun
Abstract: (InGa)2 O3 films are grown on quartz substrates by radio frequency magnetron sputtering using In/Ga2 O3 target. The crystal structure, morphology, chemical states and optical properties of (InGa)2 O3 films after annealing are investigated by X-ray diffraction, scanning electron microscopy, transmission electron microscope, X-ray photoelectron spectroscopy, optical transmission spectroscopy and photoluminescence spectroscopy. The crystallinity of (InGa)2 O3 film improves and phase segregation occurs as the annealing temperature is raised to 800 °C. A mass of cavities are formed on the surface of annealed (InGa)2 O3 films. The nanocrystal particles are found in the (InGa)2 O3 film annealed at 800 °C. The optical bandgap values of (InGa)2 O3 films change from 4.68 to 4.89 eV with increasing annealing temperature from room temperature to 800 °C, which is associated with the decrease of oxygen vacancies and loss of In component of (InGa)2 O3 films. The variation of emission band in (InGa)2 O3 films is influenced by the tunable bandgap, increasing grain boundary and phase segregation. This work investigates the effect of annealing on the optical properties of (InGa)2 O3 films and promotes the application of (InGa)2 O3 films in the optical field. Highlights: Amorphous (InGa)2 O3 films are deposited using well-designed In/Ga2 O3 target. The bandgap tunability of (InGa)2 O3 films from 4.68 to 4.89 eV is ascribed to the decrease of oxygen vacancies and loss of In atoms after annealing. The variation of emission bands in (InGa)2 O3 films with annealing temperature is associated with the tunable bandgap, increasing grain boundary and phase segregation.